Transparent megahertz circuits from solution-processed composite thin films. Issue 15 (24th March 2016) - Liu, Xingqiang; Wan, Da; Wu, Yun; Xiao, Xiangheng; Guo, Shishang; Jiang, Changzhong; Li, Jinchai; Chen, Tangsheng; Duan, Xiangfeng; Fan, Zhiyong; Liao, Lei
Abstract : Transparent high-performance amorphous metal oxide based thin-film electronics operated in the megahertz region on a 4 inch substrate. Abstract : Solution-processed amorphous oxide semiconductors have attracted considerable interest in large-area transparent electronics. However, due to its relative low carrier mobility (∼10 cm 2 V −1 s −1 ), the demonstrated circuit performance has been limited to 800 kHz or less. Herein, we report solution-processed high-speed thin-film transistors (TFTs) and integrated circuits with an operation frequency beyond the megahertz region on 4 inch glass. The TFTs can be fabricated from an amorphous indium gallium zinc oxide/single-walled carbon nanotube (a-IGZO/SWNT) composite thin film with high yield and high carrier mobility of >70 cm 2 V −1 s −1 . On-chip microwave measurements demonstrate that these TFTs can deliver an unprecedented operation frequency in solution-processed semiconductors, including an extrinsic cut-off frequency ( f T = 102 MHz) and a maximum oscillation frequency ( f max = 122 MHz). Ring oscillators further demonstrated an oscillation frequency of 4.13 MHz, for the first time, realizing megahertz circuit operation from solution-processed semiconductors. Our studies represent an important step toward high-speed solution-processed thin film electronics.